They Came to Murramarang - Hamon, Bruce (ANU Press, 2015)
Bruce Hamon's They Came to Murramarang, first published in 1994, provides a unique combination of local history and personal recollections from a writer who witnessed the transformation of the Murramarang region from the timber era to modern times. This new edition retains the original character of Bruce's engaging prose with additional chapters relating to Bruce's life, the writing of the book, the Indigenous history of the region and the transformation of the area since the book was written. The book has also been enhanced by the insertion of additional photographs.